“Photovoltaic solar systems: green energy for urban Bangladesh” - a study on Management of Global Opportunities (MGO). - Farhabi, Umme Habiba (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.